PENGARUH RATE BAGI HASIL DAN BI RATE TERHADAP DANA PIHAK KETIGA PERBANKAN SYARIAH (STUDI PADA BANK PEMBIAYAAN RAKYAT SYARIAH YANG TERDAFTAR DI BANK INDONESIA) - Ferdiansyah Ferdiansyah; Nurazlina Nurazlina; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study used a purposive sampling method or sampling based on criteria of course. The samples were is BPRS (Bank Pembiayaan Rakyat Syariah). The method used in this study, namely multiple linear regression to analyze the effect of partial with SPSS version 20.0. From the results of testing that has been done partial test (t test) showed that the variable in the Rate of Profit Sharing BPRS group that has a strong influence on the Third Party Funds. And the BI rate individually had no effect on Deposits period January 2010 - October 2013. The amount of influence that caused (R2) in the BPRS of 55%, while the remaining 45% is influenced by othervariables not included in the study.Keywords: Third Party Funds, Rate of Profit Sharing, and BI Rate